Military and Politic history of Algeria through archive documents of National Library El-Hamma (year study 1242-1243Hijri/1827AD) - kadouma, Habib (The Algerian Historical Journal, 2026)
History is the memory of people, from which the identity is sourced and the future is built. Therefore, nations value history and its documents and seek it everywhere to put it in libraries and museums. Nevertheless, in Algeria under the colonization, this resource was abused and moved overseas. Under the light of what was left or retrieved, I studied documents from Ottoman archives in the National Library of Hamma and shed some light on its scientific and historic documents, especially, the case of maritime siege, volunteers’ recruitment and Navarine battle of 1827 AD. due to its consequences on Algeria and the region overall.